Operations Management / Second Edition - Hill Terry (Palgrave Macmillan, 2005)
This book provides a comprehensive, managerial overview of the topic. Managing Operations and People for Business and Markets, Designing Services and Products and Delivery Systems, Managing and Controlling the Operation Systems, Improving Operations, Managing Operations in Practice: Long Case Studies, Acknowledgements, Index.